Leaf and Flower Characterization of Abiu (Pouteria caimito Radlk.) at Two Locations in Bogor Region, West Java, Indonesia. - Ramdan, Muhamad; Susanto, Slamet; Matra, Deden Derajat; Hapsari, Dhika Prita (Department of Agronomy and Horticulture, IPB University, 2023)
Abiu is a species introduced into Indonesia from the tropics of the Amazon and has been developing for several years. Information on the characteristics of the abiu plant are still limited compared to other introduced fruit species. This research aims to identify the characteristics of the abiu plants in two locations in the Bogor region, West Java, Indonesia. The research was conducted at Balumbang Jaya village, the sub-district of Dramaga, the village of Mekarsari, the sub district of Cileungsi, Bogor, West Java. Further observation was conducted at Post-harvest Laboratory and Micro Technic Laboratory, Department of Agronomy and Horticulture IPB. The field study was conducted in January to July of 2018. This research was descriptive and no treatment was applied on the plant samples. Sampling was done randomly with as many as 15 plants at each location. Observations and measurements were conducted on the number of branches, leaves and flowers on 10 samples per plants. The results showed that there is morphological diversity of flowers and leaves at the two locations. The length, width, and weight of leaves and flowers in Balumbang Jaya were larger than those in Mekarsari. Different environments may contribute to the diversity of abiu leaves and flowers in the two locations.